AN APOLOGETIC PRAISING OF DERRIDEAN DECONSTRUCTION - Larsen, Bente (The Nordic Journal of Aesthetics, 2022)
Review of MARTTA HEIKKILÄ, DECONSTRUCTION AND THE WORK OF ART. VISUAL ARTS AND THEIR CRITIQUE IN CONTEMPORARY FRENCH THOUGHT LONDON: LEXINGTON BOOKS 2021. 311 PAGES. ISBN: 1793619042